2023
DOI: 10.3390/agronomy13061509
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Variation of Stripe Rust Foliar and Head Infection in Egyptian Wheat as an Effect of Climate Change

Abstract: Wheat stripe rust (Puccinia striiformis Westend f. sp. tritici; Pst) is a severe disease that affects wheat-growing areas worldwide. In the last few years, Pst head infection (PstHI) was recorded to cause severe yield damage in Egypt. Little information is known about PstHI. In the current study, a set of 34 Egyptian cultivars were evaluated for their Pst foliar infection (PstFI) and PstHI in two growing seasons (2021 and 2022) in Egypt. High genotypic variations in PstFI and PstHI were found. A very weak corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This precise phenotyping that links to genotypic data in association analyses will facilitate the identification of a specific set of QTLs for complex traits [60] . The ImageJ was previously used to identify significant SNPs associated with target traits (e.g., root angle in wheat) in QTL and GWAS studies No shared markers were found between leaf and root traits [53] , [61] , [62] , [63] .…”
Section: Discussionmentioning
confidence: 99%
“…This precise phenotyping that links to genotypic data in association analyses will facilitate the identification of a specific set of QTLs for complex traits [60] . The ImageJ was previously used to identify significant SNPs associated with target traits (e.g., root angle in wheat) in QTL and GWAS studies No shared markers were found between leaf and root traits [53] , [61] , [62] , [63] .…”
Section: Discussionmentioning
confidence: 99%